Gender Differences in Student Motivation and Self-Regulation in Science Learning: A Multi-Group Structural Equation Structural Modelling Analysis - Velayutham, Sunitadevi; Aldridge, Jill; Fraser, Barry (Springer Netherlands, 2012)
The purpose of this study was to investigate the influence of students' motivational beliefs (learning goal orientation, task value and self-efficacy) in science learning on students' self-regulation in the science classroom. The study also examines the moderating effect of gender on the proposed relationships. Data were collected from 719 boys and 641 girls across grades 8, 9 and 10 in 5 public schools in Perth, Western Australia. Results from structural equation modeling analysis indicated that all 3 motivational constructs were strong predictors of students' self-regulation in science learning. The multi-group analysis to examine gender differences revealed that the influence of task value on self-regulation was statistically significant for boys only. The findings present possible opportunities for educators to plan, and to put into practice, effective intervention strategies aimed at increasing students' self-regulation in science learning. The core feature would be to target and develop students' motivational beliefs of learning goal orientation and self•efficacy in science learning. Additionally, for boys, the intervention strategies would be to elevate boys' perspectives of science task value.